2015
DOI: 10.1007/s11064-015-1792-x
|View full text |Cite|
|
Sign up to set email alerts
|

Lactate Transport and Receptor Actions in Retina: Potential Roles in Retinal Function and Disease

Abstract: In retina, like in brain, lactate equilibrates across cell membranes via monocarboxylate transporters and in the extracellular space by diffusion, forming a basis for the action of lactate as a transmitter of metabolic signals. In the present paper, we argue that the lactate receptor GPR81, also known as HCAR1, may contribute importantly to the control of retinal cell functions in health and disease. GPR81, a G-protein coupled receptor, is known to downregulate cAMP both in adipose and nervous tissue. The rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 76 publications
1
42
0
Order By: Relevance
“…12,13 However, in the early 2000s a new target for lactate was discovered, namely the receptor GPR81. Abundant GPR81 expression was recently identified the inner retina, 20 indicating that activation of GPR81 may play a prominent role in inner retinal homeostasis. Thus, we aimed to elucidate whether the lactate-linked protective effects on Müller cells were due to direct metabolism of L-lactate and/or activation through GPR81.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 However, in the early 2000s a new target for lactate was discovered, namely the receptor GPR81. Abundant GPR81 expression was recently identified the inner retina, 20 indicating that activation of GPR81 may play a prominent role in inner retinal homeostasis. Thus, we aimed to elucidate whether the lactate-linked protective effects on Müller cells were due to direct metabolism of L-lactate and/or activation through GPR81.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mRNA expression levels of GPR81 have also been quantified in retinas obtained from mice. 20 However, in this study, we aimed to verify the presence of the receptor and possible regulations in response to altered levels of energy availability. Deprivation of glucose led to increased GPR81 expression, indicating an amplification of lactate-mediated effects through GPR81 activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent studies have suggested a neuroprotective role of lactate in the retina (Kolko et al. ; Vohra & Kolko ; Vohra et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…GPR81 is expressed at much lower levels in the brain, where it seems to be involved in neuronal signalling, as well as the retina where it has been implicated in regulation of blood flow to meet metabolic demands (17)(18)(19)(20). It is also induced in several cancer types where it appears to play a role in the adaptation to the ischemic tumor microenvironment (21).…”
Section: Introductionmentioning
confidence: 99%